A apropriação econômica do território pela Cooperativa Agrária Agroindustrial, em Entre Rios / Guarapuava (PR) - Kaminski, Marisa Pereira (2012)
This research shows the economic ownership of the territory by the Agrária Agroindustrial Cooperative, located in the Entre Rios district, in Guarapuava, in the south- central part of Paraná. Assumptions that this appropriation includes territorial strategies and relational process conforming the Agrária Cooperative`s territorialities. In search of answers,this study was guided in the Haesbaert conceptions (2004), that deals with the multiple territorialities, in their political, economic and cultural ways, influencing the production in the territory, but mainly in Saquet (2002, 2003), which highlights, between those dimentions, the economic aspect. Agrária was founded by the Danube Swabians ( people with German language and German culture), it is one of the cooperatives in Paraná founded by immigrants. Such cooperatives were inspired by the nineteenth- century European associations,with its organizational peculiarities invoving the group organizational cohesion in relation to the work and the query of ethnocultural identity. Nevertheless, by the economic appropriation of the territory, Agrária has articulated some territorial strategies directed to the productionfor the large markets, and their relational process has generated some internal conflicts. This daily mode of action in the cooperative is in the midst of the organization, appropriation, and the space domination shaping the territoriality, with social and economic dimentions, that affects directly, and locally, the Entre Rios district.